The enrichment of cancer stem cells using composite alginate/polycaprolactone nanofibers. (15th February 2019) - Hu, Wei-Wen; Lin, Cheng-Hsien; Hong, Zhen-Jie
Highlights: Cell adhesion and distribution are controlled by the composition of alginate/PCL fibers. Cancer stem cells (CSCs) are enriched by alginate and composite fibers. Cells from composite fibers with low ratio of PCL exhibited improved CSC property. Abstract: Cancer stem cells (CSCs) are potential platforms to high-throughput screen anti-cancer drugs. However, they are difficult to isolate from cancer cells. Therefore, we proposed to fabricate 3-D scaffolds for CSC enrichment. Alginate is a biocompatible polysaccharide with poor cell adhesion, whereas polycaprolactone (PCL) is relative cell adhesive. These two materials were coelectrospun as composite scaffolds. Cells collected from alginate and composite fibers demonstrated high stemness, epithelial-mesenchymal transition, invasion, drug resistance, and angiogenesis. Interestingly, cells collected from composite fibers with low ratio of PCL were significantly improved their CSC properties compared to those from pure alginate fibers because few PCL fibers spatially separated cell populations to concentrate CSCs. These results suggested that alginate fibers effectively enriched CSCs and composite fibers created an uneven microenvironment to regulate cell morphology and distribution, by which cell-cell interaction was thus manipulated. These tunable scaffolds are potential to isolate CSCs from different tissues to facilitate the cancer research.